Oxidative stress may be a contributing factor in fibromyalgia patients' pain mechanisms - H. Beyaztas; S. Aktas; E.M. Guler; E. Ata (PAGEPress Publications, 2023)
Objective. The pathophysiology of fibromyalgia (FM), a continuously painful syndrome with no known origin, has been related to mitochondrial dysfunction, oxidative stress, and inflammation. Recent studies have shown that FM may be associated with an oxidative balance disorder. The objective of this study was to measure the levels of oxidative stress in FM patients and try to understand the association between FM and free radicals. Methods. This study was performed on 100 volunteers admitted to the University of Health Sciences, Sultan 2, Abdulhamid Han Health Application and Research Center Physical Therapy and Rehabilitation Clinic, including 50 healthy controls and 50 patients with FM. To analyze oxidative stress biomarkers, total oxidant status (TOS) and total antioxidant status (TAS) levels were measured. Total thiol (TT) and native thiol (NT) concentrations were measured to determine the relationship between thiol groups. Disulfide (DIS) and oxidative stress index (OSI) were calculated with mathematical formulas. Results. While TOS and OSI levels were statistically higher in FM patients, TAS levels were significantly lower compared to the healthy control group (p<0.001). In comparison to the healthy control group, FM patients had considerably decreased TT and NT levels. DIS levels were significantly higher in FM patients than in controls (p<0.001). Conclusions. Reactive oxygen species have several negative impacts on the human body. As a result of the measurements we analyzed, the relationship between FM and oxidative stress should be studied in terms of disease progression and may help improve the treatment process.